Friction - Brown, Sandra, 1948- (New York : Grand Central Publishing, 2015)
Crawford Hunt wants his daughter back. Following the death of his wife four years ago, Crawford, a Texas Ranger, fell into a downward spiral that left him relegated to deskwork and with his five-year-old daughter Georgia in the custody of her grandparents. But Crawford has cleaned up his act, met all the court imposed requirements, and now the fate of his family lies with Judge Holly Spencer.
Keywords: Custody of children -- Fiction; Women judges -- Fiction; Romantic suspense fiction